2012
DOI: 10.1111/j.1532-950x.2012.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Epsilon Aminocaproic Acid for the Prevention of Delayed Postoperative Bleeding in Retired Racing Greyhounds Undergoing Gonadectomy

Abstract: Postoperative administration of EACA significantly decreased the prevalence of postoperative bleeding in RRG undergoing surgery by increasing the clot strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 35 publications
(51 reference statements)
3
42
0
1
Order By: Relevance
“…Therefore, the accuracy of TEG for diagnosis of clinical hyperfibrinolysis is questionable, and a previous study failed to detect substantial lysis by use of TEG in dogs that responded favorably to treatment with anti-fibrinolytic drugs. 12 More recently, modified TEG assays using additional tPA have revealed measurable differences in TEG fibrinolysis variables between human and canine patients with disorders of fibrinolysis and healthy subjects. 14,21 By use of a similar approach, our qualitative tPA dose-response analysis of canine and human plasma revealed that higher tPA concentrations resulted in more profound decreases in MA, TG, and MRTG in canine plasma than in human plasma, but the TEG tracings had similar shapes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the accuracy of TEG for diagnosis of clinical hyperfibrinolysis is questionable, and a previous study failed to detect substantial lysis by use of TEG in dogs that responded favorably to treatment with anti-fibrinolytic drugs. 12 More recently, modified TEG assays using additional tPA have revealed measurable differences in TEG fibrinolysis variables between human and canine patients with disorders of fibrinolysis and healthy subjects. 14,21 By use of a similar approach, our qualitative tPA dose-response analysis of canine and human plasma revealed that higher tPA concentrations resulted in more profound decreases in MA, TG, and MRTG in canine plasma than in human plasma, but the TEG tracings had similar shapes.…”
Section: Discussionmentioning
confidence: 99%
“…7,26 However, recently the ability of EACA to reduce clinical postoperative bleeding in Greyhounds has been determined in a retrospective analysis of limb amputations and a prospective, randomized clinical trial of dogs undergoing elective ovariohysterectomy or orchiectomy. 11,12 Given the lack of pharmacokinetic and pharmacodynamic data in dogs, doses were extrapolated from human data. 27 The data presented here suggest that this may result in suboptimal plasma concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EACA is a medication that is approved by the Food and Drug Administration (FDA) primarily for the treatment of ovulatory bleeding (14). Many previous studies have recommended it for the prevention of fibrinolysis and bleeding (15)(16)(17)(18). EACA is an antifibrinolytic analogue of lysine and prevents activation and conversion of plasminogen to plasmin on fibrin surface (19).…”
Section: Discussionmentioning
confidence: 99%
“…Delayed (2-3 days) postoperative bleeding in retired racing greyhounds has been reported and has been posited to be caused by hyperfibrinolysis. 97,98 It is not possible to predict which dogs will experience delayed bleeding, but it is wise to closely monitor sighthounds in the postoperative period. Drugs such as epsilon-aminocaproic acid or tranexamic acid may be useful to mitigate hyperfibrinolysis in some cases.…”
Section: Disorders Of Fibrinolysismentioning
confidence: 99%